Peran Masyarakat dalam Pengembangan Lembaga Pendidikan Islam di MA NW Bungtiang - Maryam; Imi Mistura; M. Saipul Watoni (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Islamic educational institutions play an important role in strengthening the scientific, moral and spiritual foundations of society. However, the development of these institutions requires significant contributions from the community to achieve their maximum potential. This article presents the research method used, which is qualitative with a descriptive approach and uses interview, observation and documentation data collection techniques. Apart from that, this research also aims to find out about the role of the community in the development of Islamic Education Institutions at MA NW Bungtiang, what are the supporting factors and barriers to Community participation in the development of the MA NW Bungtiang Educational Institution and to find out how the school overcomes obstacles to the Community's role in developing the Islamic Educational Institution at MA NW Bungtiang. The results of this research show that the analysis of the role of society in the development of Islamic educational institutions takes into account key aspects such as financial support, active participation in educational activities, as well as increasing awareness of the importance of Islamic education. Through strong community involvement, Islamic educational institutions can become centers of sustainable educational excellence, creating a generation that is intellectually, morally and spiritually strong for a better future.